An E-Book Building Methodology Using An Extensible Personalization Structure For Operationalizing E-Book Interface Mataphors - Hameed, M. Noorul (2010)
An electronic book (or e-book) presents traditional book structures/functions in digital form. In digital form, it is able to include multimedia/hypermedia services as well as other special features. Present e-book frameworks have shortcomings in their representation format, especially for academic e-publishing. The problems include the ebook personalization by user, the support for e-book publisher and the file format. Users may require additional capabilities such as e-book structuring and layout. E-book does not provide a flexible layout to content developers to come out with an e-book personalization structure. However, e-book personalization requires a file format for digital content representation, portability and interoperability. In order to address these problems, this thesis aims to identify requirements of personalization elements, to represent e-book personalization, to formalize e-book personalization components, and to develop e-book packaging control and standards. These are achieved in three phases: the representation/personalization, builder specification, and e-book practical analysis.